DOES BOARD STRUCTURE FOSTER ENVIRONMENTAL INITIATIVE AND MITIGATE FINANCIAL RISK? - Valentine Siagian; Judith Tagal Gallena Sinaga; James Sylvanus Uly Reke (Jurnal Bisnis dan Akuntansi, 2025)
This study examines whether board structure serves as an effective governance mechanism in promoting environmental initiatives and mitigating financial risk among publicly listed firms in Indonesia. Drawing on Agency Theory and Stakeholder Theory, it explores how board independence, size, and gender diversity shape sustainability-oriented decisions and financial outcomes. A quantitative research design is employed using secondary panel data from 161 firm-year observations over the period 2013–2024. The study analyzes the impact of board characteristics on the adoption of emission-reduction initiatives and financial risk, proxied by leverage, using empirical regression. Results show that board independence and size are associated with greater emission reductions, suggesting that better governance enhances accountability. However, there is no clear, direct link between board traits and financial risk, implying that board structure alone does not drive stability. This study extends ESG research in emerging markets by showing that governance has different roles in environmental and financial matters. It suggests boards should be strengthened to support sustainability, while financial results may depend on broader factors.